La quiebra transnacional - Dasso, Ariel Gustavo (2011)
In a globalized world where relationships are cross-border in nature, there is concern on the part of signatories of trade agreements with the so-called transnational bankruptcy in which the assens of the insolvent company are placed in different and distant parts of the world, giving rise to an urgent and necessary legal reciprocity between states, because otherwise the effects on property would make any action relating to the bankruptcy, or «concordato» (agreement with creditors) proceedings, worthless. In Argentina current laws are not in line with contemporary reality, since they are laws which protect nationals, and which are inoperative in processes involving the bankruptcy of foreigners, access to justice of foreign administrators, and the reciprocal cooperation between Argentine and foreign justice. Nor does it make possible the bankruptcy of a debtor domiciled abroad but with property in Argentina. Argentina’s legislation requires its institutions to get up to date, abandon outdated protectionist laws, and get into line with contemporary commercial reality in accordance with the model law of UNICITRAL.